(untitled) (Bangladesh Heart Journal, 2022)
Objective: The aim was to evaluate the early outcome of off-pump coronary artery bypass grafting (OPCABG) with a bilateral internal mammary artery (BIMA) Y configuration graft to achieve total arterial myocardial revascularization. Materials and Methods: From March 2018 to March 2020 total 30 cases of off pump CABG surgery using LIMA RIMA Y sequential grafts to achieve total arterial myocardial revascularization. Comparisons between LIMA + SVG and BIMA Y grafts were not made here. Result: The average age of the patients was 43.51±2.58 years. Most of them were male (93.34%). A total of 28 (93.34%) cases had triple-vessel disease. Double-vessel disease was found in 2 (6.66%) cases. The skeletonization skill was used to harvest the two IMAs and then the free right internal mammary artery was anastomosed end-to-side to the in situ left internal mammary artery to composite a Y configuration graft. Off-pump and sequential anastomosis methods were used to perform coronary artery bypass surgery for the patients. Graft patency was assessed by doing CT angiogram. All distal and proximal Y anastomoses were patent at 1 year follow up. There were no perioperative deaths. Conclusion: OPCABG by using LIMA RIMA Y graft is an effective option for total arterial revascularization and avoid surgical complications regarding the ascending aorta manupulation. Bangladesh Heart Journal 2022; 37(1): 27-33